Examining the Effects of Total Quality Management on Operational Performance, Quality Performance, and Employee Performance - Nurullaily Kartika; Faradilah Hanum (Lembaga Publikasi Ilmiah Nusantara, 2026)
The banking sector is one of the most significant service industries contributing to a country's economic development. The increasing complexity of banking operations necessitates continuous improvements in organizational quality to remain competitive in an increasingly globalized business environment. One of the most widely adopted approaches to enhancing organizational quality is Total Quality Management (TQM). TQM can be implemented in all industries, including service industries. Banks primarily provide intangible services; thus, their operational performance encompasses not only financial metrics but also service quality. This study examines the relationship between TQM practices and operational, quality, and employee performance in conventional commercial banks in Indonesia. This study uses Structural Equation Modeling (SEM) as the statistical analysis technique, and the sample consists of 300 employees from several conventional commercial banks in Indonesia. The findings indicate that TQM practices are positively associated with operational and employee performance in the banking sector.